Assessment of changes in land cover and land use in the Blanco River basin using satellite classifications between 2000 and 2022 (Semiárida, 2025)
Globally, land cover and land use changes are the main direct driver of biodiversity loss, with wetlands being particularly vulnerable ecosystems. The objective of this work was to analyze land cover changes in the Blanco River Basin between 2000 and 2022, with a focus on the wetland class, by using quantitative remote sensing tools and geographic information systems. The basin has high Andean wetlands that have shown a severe deterioration in their conservation status in the last decades. The methodology consisted of producing a supervised classification using multispectral data from the Landsat series (2000-2022), and comparing it with the classification provided by the MapBiomas Argentina project. In addition, the landscape metrics ‘Total Class Area’ and ‘Landscape Percentage’ were calculated for each class and year evaluated. The results show that wetlands decreased by 263 ha (36.4 %) during the study period, mainly due to the spread of rosehip and conversion to pastureland. This work provides useful data for a broader assessment of degradation in the Blanco River basin. The findings may help inform land-using planning strategies aimed at conserving the region’s wetlands.
Keywords: Degradation; high altitude meadows; landscape; remote sensing